The Controversy Over Village Officials' Intervention in the Marriage of Adulterous Couples: A Study of Islamic Law in Aceh - Nurhadisah (International Journal of Sharia Studies, 2025)
Marriage in Islam is a sacred bond that aims to maintain honor and offspring in accordance with sharia. Adultery is seen as an act that damages the moral order and is strictly prohibited in Islam and in Law Number 1 of 1974 concerning Marriage. This study aims to analyze the forms of intervention of village officials in the marriages of adulterous couples in Pulo U Village, Pidie Jaya Regency, and examine this practice from the perspective of Islamic law. The research method used is descriptive qualitative, with data collection through interviews, field observations, and library research of Islamic law literature and the Aceh Qanun Jinayat. The results show that village officials more often use reusam (customary law) than Qanun Jinayat in handling adultery cases, because it is considered more flexible, faster, and able to maintain community honor. However, the practice of this intervention often results in violations of Islamic law principles, such as violations of privacy, social violence, and forced marriages against adulterers. From the perspective of Islamic family law, forced marriages do not fulfill the element of consent of both parties, and are therefore invalid according to the majority of scholars. Therefore, the resolution of adultery cases should be carried out by upholding justice, public interest, and sharia principles without ignoring individual rights and human values.